2008
DOI: 10.1002/prot.22110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of similarity/dissimilarity of protein sequences

Abstract: On the basis of a selected pair of physicochemical properties of amino acids, we introduce a dynamic 2D graphical representation of protein sequences. Then, we introduce and compare two numerical characterizations of protein graphs as descriptors to analyze the nine ND5 proteins. The approach is simple, convenient, and fast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…On the other hand, we found that the difference of ND5 protein between specie (9) and other species are greatest. In addition, the results obtained from numerical experiments are consistent with the fact of biological evolution [11,12], which also demonstrates the effectiveness of this method to some extent.…”
Section: Resultssupporting
confidence: 73%
“…On the other hand, we found that the difference of ND5 protein between specie (9) and other species are greatest. In addition, the results obtained from numerical experiments are consistent with the fact of biological evolution [11,12], which also demonstrates the effectiveness of this method to some extent.…”
Section: Resultssupporting
confidence: 73%
“…If the points are all around the trend line, this shows that the correlation is better. Observing the figure, our method presented higher correlation with Clustal W than the methods of Hou et al, 5 Elmaatv et al, 6 Wen et al method, 7 Zhang et al method, 8 Wu et al, 9 Yao et al, 10 and He et al 14 …”
mentioning
confidence: 66%
“…Wu et al 9 proposed a two-dimensional graph, called "2D-MH" to compare the evolutionary distances between any number of protein sequences. Yao et al 10 introduced a dynamic 2D graphical representation based on physicochemical properties of amino acids and compared the sequences of nine ND5 proteins. Mu et al 11 compared the similarity/dissimilarity of protein sequences according to the distance frequency of amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…For large proteins, it is not a visual representation and is not directly related to similarity of sequences. Yao et al [22] introduced a dynamic 2D graphical representation of protein sequences based on the pKa values used by Randić. This dynamic approach can help us to inspect the data and recognize the major similarities among different proteins.…”
Section: Introductionmentioning
confidence: 99%